مذابح صبرا وشاتيلا سنة 1982 وقائعها وانعكاساتها - • تمار ليليا (جامعة محمد بوضياف بالمسيلة, 2025)
تشكل مجزرة صبرا وشاتيلا (16–18 أيلول/سبتمبر 1982) إحدى أبشع الجرائم في التاريخ المعاصر، حيث استُهدِف مدنيون فلسطينيون ولبنانيون عُزّل في المخيمين تحت حصار الجيش الإسرائيلي وبعد انسحاب منظمة التحرير الفلسطينية. أسفرت المجزرة عن مقتل ما بين 2000 و3500 ضحية، ونفذتها ميليشيات لبنانية بتغطية إسرائيلية. لم تكن المجزرة حدثًا معزولًا، بل ثمرة سياق معقّد من الحرب الأهلية اللبنانية والاجتياح الإسرائيلي للبنان والتواطؤ الدولي. وقد خلّفت انعكاسات عميقة: سياسيًا عززت خطاب المقاومة ورفض التسويات، وإنسانيًا رسخت مأساة في الذاكرة الجماعية الفلسطينية واللبنانية، ودوليًا كشفت عجز القانون الدولي وازدواجية المعايير. The Sabra and Shatila massacre (September 16–18, 1982) stands as one of the most horrific crimes in modern history, where defenseless Palestinian and Lebanese civilians were targeted in the two camps under the siege of the Israeli army, shortly after the withdrawal of the Palestine Liberation Organization. The massacre, carried out by Lebanese militias with Israeli cover, left between 2,000 and 3,500 victims. It was not an isolated event but rather the outcome of a complex context involving the Lebanese Civil War, the Israeli invasion of Lebanon, and international complicity. The massacre had profound repercussions: politically, it reinforced the discourse of resistance and rejection of settlements; humanly, it left a lasting trauma in Palestinian and Lebanese collective memory; and internationally, it exposed the impotence of international law and the double standards of the global system.